Barley: Global challenges and perspectives under non-tropical dry areas - Verma, Ramesh Pal Singh (Journal of Cereal Research, 2018)
The International Center for Agricultural Research in Dry Areas (ICARDA) is one of the 15 CGIAR centers and has a global mandate for barley improvement, specifically for more than 16 million ha of barley is grown in non-tropical dry areas across the globe. ICARDA’s barley improvement program has been reorganized into spring barley for high and low input environments and winter barley programs to address the requirements of different agro-climatic conditions/regions. The spring barley program targets germplasm improvement for feed, food and malt purposes, targeting germplasm enhancement for global stressed environments in hulled and huskless barley. The winter barley program is basically focused to improve germplasm for colder regions in West and Central Asia where cold and frost are the major stresses along with drought. Each year, nearly 10000 advanced lines are evaluated for various agronomic, biotic and abiotic stress tolerances, and grain quality parameters in the breeding program. ICARDA’s gene bank holds more than 33,000 barley accessions of which 2042 accessions are wild relatives of barley. The Focused Identification of Germplasm Strategy (FIGS) approach is utilized to mine efficiently this collection by selecting manageable subsets with higher frequencies for finding the sought traits. ICARDA’s barley improvement program annually shares more than 330 sets of international trials and nurseries, with more than 60 collaborators in 35 to 40 countries. During 1977-2018, more than 269 barley varieties have been released across the globe by different countries, with direct introduction of germplasm from ICARDA’s barley breeding programs, out of which 53 are released during last 10 years. In recent year, ICARDA’s feed and food barley improvement program aims at improving nutritional qualities of barley, specifically Zn, Fe, and β-Glucan contents. Simultaneously, the malt barley improvement is targeting to identify better malting quality germplasm for developing countries in Africa and Asia with a possibility of additional income to farmers through premium price for better quality in East Africa and South Asia. Doi.org/10.25174/2249-4065/2018/85893